Boron and a Current Overview of its Effects On Health - YARAT, AYŞEN (AVES PRESS LTD, 2017)
Boron is an element that naturally exists as compounds and has the most reserves in our country. Boron compounds are used in glass, ceramics, cleaning, whitening, cosmetic, metallurgy, nuclear, computer, aircraft, energy, agricultural, and health industries. It enters the body through nutrients and drinking water. Recent studies have focused on the biological importance of boron and its positive effects on human health and have emphasized the importance of its role in mineral and hormone metabolisms, bone development, antioxidant defense system, wound healing, energy metabolism, and immune system. Here we review the importance of boron in our nutrition and its effects on health.
Keywords: Boron; health; diet; food and nutrition; DIETARY BORON; TURKEY; FOODS; RATS; HUMANS; RISK